Non-linearities in the relation between the exchange rate and its fundamentals - Carlo Altavilla; Paul De Grauwe (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper investigates the relationship between the euro-dollar exchange rate and its underlying fundamentals. First, we develop a simple theoretical model in which chartists and fundamentalists interact. This model predicts the existence of different regimes, and thus nonlinearities in the link between the exchange rate and its fundamentals. Second, we account for non-linearity in the exchange rate process by adopting a Markov-switching vector error correction model (MSVECM). Finally, the paper investigates the out-of-sample forecast performance of three competing models of exchange rate determination. The results suggest the presence of nonlinear mean reversion in the nominal exchange rate process. The implications are that different sets of macroeconomic fundamentals act as driving forces of the exchange rates during different time periods. More interestingly, the nonlinear specification significantly improves the forecast accuracy during periods when the deviation between exchange rate and fundamentals is large. Conversely, when the exchange rate is close to its equilibrium value it tends to be better approximated by a na?ve random walk.
Keywords: C32; F31; 330; non-linearity; Markov-switching model; fundamentals; Wechselkurs; Devisenmarkt; Mikrostrukturanalyse; Schätzung; Theorie; EU-Staaten; USA